Screening of Beta Satellite Associated DNA-A Chili Leaf Curl Virus from Maharashtra - Shingote, Prashant R.; Wasule, Dhiraj L.; Rathod, Darasing R.; Gaharwal, Anjali M.; Ghawade, Shyam M.; Gahukar, Santosh J. (International Journal of Bio-resource and Stress Management, 2024)
The experiment was conducted during October–November 2023 at Vasantrao Naik College of Agricultural Biotechnology (Dr. PDKV, Akola), Waghapur Road, Yavatmal (445001), Maharashtra, India. The Chilli leaf curl disease (ChiLCD) has become a major disease of Chilli (Capsicum annum L.) throughout India. The present study aimed at precise identification and molecular characterization of Chilli leaf curl virus (ChiLCV) as it is responsible for a serious menace by causing significant loss of yield in various chilli growing districts of Maharashtra. The ChiLCD affected chilli plants were showing various symptoms such as leaf curl, smaller leaves, stunting of a plant with a smaller number of flowers and fruits. During rabi season (October 2022–February 2023) of 2022–23 sample surveys were conducted and infected samples from different regions were collected from affected fields and subjected to a polymerase chain reaction (PCR) using coat protein (CP), DNA-A, DNA-B and betasatellite specific primers. Out of 9 samples taken for the study 6 samples were amplified with 520 bp size amplicon corresponding to CP gene. The 520 bp amplicon were gel eluted and sequenced. Database searches were done by using BLAST analysis in which sequence revealed 99% similarity with ChiLCV isolates existing in GenBank database. Sequence analysis of the CP gene revealed the identity of ChiLCV associated with the ChiLCD of chilli crop in Maharashtra, India. Moreover, the phylogenetic analysis suggested the clustering of these isolates from two different regions within the same clade were found to correspond to the ChiLCV begomovirus belonging to the family Geminiviridae. The PCR results indicated that ChiLCV from Maharashtra governs monopartite DNA-A genome along with betasatellite molecule.